Pattern of congenital malformations in newborn: a hospital-based study - Mohamed El Koumi; Ehab Al Banna; Ibrahim Lebda (MDPI AG, 2013)
Background: Birth defects, encountered frequently by pediatricians, are important causes of childhood morbidity and mortality. Birth defects can be classified based on their severity, pathogenic mechanism or whether they involve a single system or multiple systems. This hospital based prospective descriptive study highlights the prevalence of congenital anomalies (CAs) in one year, among liveborn neonates delivered in a university hospital. Design and methods: All women giving birth to babies were included. Demographic details, associated risk factors and the type of CAs in babies were recorded. Diagnosis of CAs was based on clinical evaluation, radiographic examination and chromosomal analysis of newborn whenever recommended. Results: The overall incidence of CAs among liveborn neonates was 2.5%, as most of the cases were referred to Zagazig University Hospital for delivery. The musculoskeletal system (23%) was the most commonly involved; followed by central nervous system (20.3%). Involvement of more than one system was observed in (28.6%) cases. Out of the maternal and fetal risk factors, parental consanguinity, maternal undernutrition and obesity, positive history of an anomaly in the family, low birth weight(LBW), and prematurity were significantly associated with higher frequency of CAs(p <0.05), with non-significant differences for maternal age and the sex of the neonates. Conclusion : The current study highlighted the point prevalence of congenital anomalies in one year in zagazig university hospital in Egypt. The present study revealed a high prevalence of congenital anomalies in our locality and stressed upon the importance of carrying out a thorough clinical examination of all neonates at birth.